Augmented Reality (AR) Learning: Improving Students Memory in Science Learning at the Elementary School Level - Nurul Athiyah; Nala Ni’matul Maula; Abdul Khobir; Juwita Rini (Pengembangan Pendidikan dan Pembelajaran Sekolah Dasar, 2024)
Education as one of the fields that is also affected, adapts to the rapid advancement of technology, ranging from curriculum changes to the use of various learning resources and technology-based learning media. One of the innovations that has emerged is the use of Augmented Reality (AR) as a learning medium. This study aims to evaluate the effectiveness of the use of AR in improving students' memory of learning materials.  The method used in this study is the Kurl Lewin model action learning research method with a qualitative experimental approach that positions teachers to play an active role in implementing learning problem-solving interventions that occur in the learning of grade V students of SD Negeri Panjang Wetan 03 Pekalongan. The findings of this study show that AR media can facilitate students in understanding and remembering science material. In addition, AR is also effective in describing abstract concepts that are difficult to practice or observe directly. The implications of this research can be the basis for educators, policy makers, and learning media developers to implement AR technology more widely in the learning process, in order to improve the quality of education and enrich the learning experience of students.